2020
DOI: 10.1038/s41598-020-76428-0
|View full text |Cite
|
Sign up to set email alerts
|

Deviant reporter expression and P2X4 passenger gene overexpression in the soluble EGFP BAC transgenic P2X7 reporter mouse model

Abstract: The ATP-gated P2X7 receptor is highly expressed in microglia and has been involved in diverse brain diseases. P2X7 effects were also described in neurons and astrocytes but its localisation and function in these cell types has been challenging to demonstrate in situ. BAC transgenic mouse lines have greatly advanced neuroscience research and two BAC-transgenic P2X7 reporter mouse models exist in which either a soluble EGFP (sEGFP) or an EGFP-tagged P2X7 receptor (P2X7-EGFP) is expressed under the control of a B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In addition, it has been reported P2X4R negative mice with increased P2X7R expression with passenger mutations altering the receptor’s function ( Er-Lukowiak et al, 2020 ; Ellegaard et al, 2021 ). Similar results were obtained using a transgenic mouse line that expresses soluble GFP by P2X7R promoter, increasing the expression of P2X4R ( Ramírez-Fernández et al, 2020 ). However, has been reported a concomitant decrease in the expression of P2X4R and 7 in liver and kidney of mice deficient for P2X4R or 7 ( Craigie et al, 2013 ; Besnard et al, 2016 ).…”
Section: Introductionsupporting
confidence: 76%
“…In addition, it has been reported P2X4R negative mice with increased P2X7R expression with passenger mutations altering the receptor’s function ( Er-Lukowiak et al, 2020 ; Ellegaard et al, 2021 ). Similar results were obtained using a transgenic mouse line that expresses soluble GFP by P2X7R promoter, increasing the expression of P2X4R ( Ramírez-Fernández et al, 2020 ). However, has been reported a concomitant decrease in the expression of P2X4R and 7 in liver and kidney of mice deficient for P2X4R or 7 ( Craigie et al, 2013 ; Besnard et al, 2016 ).…”
Section: Introductionsupporting
confidence: 76%
“…Although in both P2X7 reporter models the EGFP constructs are expected to be expressed under the control of the P2rx7 promoter, there were substantial differences in their cell-type-specific expression, and serious concerns were raised regarding the reliability of the reporter expression in the sEGFP mouse (Ramirez-Fernandez et al, 2020 ). For example, the sEGFP model overexpresses a P2X4 passenger gene, and sEGFP shows clear neuronal localization, but appears to be absent in microglia.…”
Section: Knockout and Transgenic P2x7 Receptor Mice Modelsmentioning
confidence: 99%
“…The qPCR results from mRNA demonstrated that the overexpression of Cdx1 is essentially derived only from exons 2 and 3 of Cdx1 ( Figure 4 B), indicating that Cdx1 overexpression is derived from the BAC transgene. An increase in the gene copy number generally results in upregulated expression, sometimes disproportionately higher in a tandem arrangement ( Loehlin and Carroll, 2016 ), and the “passenger genes” on BAC clones are known to be upregulated in BAC transgenic mice ( Farrar et al., 2021 ; Gong et al., 2010 ; Ramirez-Fernandez et al., 2020 ). In addition, considering the fact that the upregulation of Slc6a7 , Arsi , and Cdx1 unnaturally stands out in terms of fold change and reliability compared to more mild and variable changes in other genes in RNA-seq analysis ( Figure S3 B and Table S1 ), it is highly likely that a significant proportion of these upregulated genes is the result of multiplied copy number of genes from the integrated BAC transgene.…”
Section: Resultsmentioning
confidence: 99%